A Revision of Kola Babarinde's Stance on Value Statements In Education - Ikeoluwapo B. Baruwa (Faculty of Teacher Training and Education, Universitas Terbuka, 2020)
The place of value statements in education cannot be undermined and should consequently not be overemphasized. Value statements have been characterized to be part of most educational discussions and writings, however, its centrality should not be hindered (rather worked on) as conceived and supported by some philosophers, as against the logical positivists or empiricists who considered it to be a mere expression of thoughts. As the popular saying is, when the purpose of a thing is not known, abuse becomes inevitable; this paper seeks a revision of Kola Babarinde’s stance on value statements in education, and further emphasizes the position value plays in the contemporary schools.